The complex structure of the disk around HD 100546 - Benisty, M.; Tatulli, E.; Ménard, F.; Swain, M. R. (Astronomy and astrophysics (Berlin), 2010)
Context. Disclosing the structure of disks surrounding Herbig AeBe stars is important to expand our understanding of the formation and early evolution of stars and planets. The first astronomical units of these disks in particular, because they are hot, dense, and subject to intense radiation field, hold critical clues to accretion and ejection processes, as well as planet formation in environment different than what prevailed around our own early Sun. Aims. We aim at revealing the sub-AU disk structure around the 10 Myr old Herbig Be star HD 100546 and at investigating the origin of its near and mid-infrared excess. Methods. We used new AMBER/VLTI observations to resolve the K-band emission and to constrain the location and composition of the hot dust in the innermost circumstellar disk. Combining AMBER observations with photometric and MIDI/VLTI measurements from the litterature, we revisit the disk geometry using a passive disk model based on 3D Monte-Carlo radiative transfer (including full anisotropic scattering). Results. We propose a model that includes a tenuous inner disk made of micron-sized dust grains, a gap, and a massive optically thick outer disk, that successfully reproduces the interferometric data and the SED. We locate the bulk of the K-band emission at ~0.26 AU. Assuming that this emission originates from silicate dust grains at their sublimation temperature of 1500 K, we show that micron-sized grains are required to enable the dust to survive at such a close distance from the star. As a consequence, in our best model, more than 40% of the K-band flux is related to scattering, showing that the direct thermal emission of hot dust is not always sufficient to explain the near-infrared excess. In the massive outer disk, large grains in the mid-plane are responsible for the mm emission while a surface layer of small grains allows the mid and far infrared excesses to be reproduced. Such vertical structure may be an evidence for sedimentation. The interferometric observations are consistent with a disk model that includes a gap until ~13 AU from the star and a total dust mass of ~0.008 lunar mass (~$6.10^{23}$ g) inside it. These values together with the derived scale height (~2.5 AU) and temperature (~220 K) at the inner edge of the outer disk (r=13 AU), are consistent with recent CO observations.